2017
DOI: 10.1021/acs.est.7b03667
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic in the North Atlantic Subtropical Gyre

Abstract: Plastics can be found in all ecosystems across the globe. This type of environmental pollution is important, even if its impact is not fully understood. The presence of small plastic particles at the micro- and nanoscales is of growing concern, but nanoplastic has not yet been observed in natural samples. In this study, we examined four size fractions (meso-, large micro-, small micro-, and nanoplastics) of debris collected in the North Atlantic subtropical gyre. To obtain the nanoplastic portion, we isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
418
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(456 citation statements)
references
References 52 publications
6
418
2
2
Order By: Relevance
“…Ter Halle et al 10 . However, these authors did not perform static light scattering measurements and were therefore not able to quantitatively estimate the concentration of colloidal particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ter Halle et al 10 . However, these authors did not perform static light scattering measurements and were therefore not able to quantitatively estimate the concentration of colloidal particles.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that nanoplastics with a broad range of sizes were produced over a period of weeks. More recently, Ter Halle et al 10 investigated seawater collected near the surface of the North Atlantic subtropical gyre. The seawater was filtered through 1.2 µm pore size filters, and the filtrate was inspected for the presence of nanoplastics with dynamic light scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nanoplastics have been shown to traverse food webs from algae to zooplankton to planktivorous fish to piscivorous fish 54 and can cause changes in the behaviour and metabolism of the fish along this feeding chain. 54 It is extremely difficult to identify nanoplastics in biological samples, 55 in part because of their small size and also that they are chemically very similar overall to organic matter, and furthermore, merely knowing that they are nanoplastics is not enough, since they must be further identified in terms of their chemical structures. From a survey of the literature, just one study appears to have been published to date, reporting the successful detection and chemical identification of nanoplastics in an actual environmental sample, which consisted of water taken from the North Atlantic Subtropical Gyre ( Figure 5).…”
Section: Nanoplasticsmentioning
confidence: 99%
“…Changes in the pyrolytic signals of PE with decreasing debris size were also noted, and it was concluded that this might be a result of structural modification of the plastic by weathering processes. 55 A review 56 has been made of recent developments in the separation and analysis of microplastics and nanoplastics, with particular reference to their determination in 'complex samples', such as organisms sampled in the field, and wastewater. A combination of different techniques is recommended, and it is suggested that methodological experience gained in different disciplines might be useful, such as cellular and molecular biology, which routinely employ separation techniques on the microscale and nanoscale.…”
Section: Nanoplasticsmentioning
confidence: 99%
“…Pollution by plastic litter has become a major environmental problem resulting from their accumulation in terrestrial and marine environments. The fragmentation of plastics into microplastics is the most challenging issue [1][2][3][4][5][6][7][8][9] : in addition to the fact that microplastics are impossible to remove from the ocean, which is their ultimate receptacle, they are even more damaging than the macro waste. .…”
Section: Introductionmentioning
confidence: 99%